KEPEMIMPINAN PROFETIK ISLAM OLEH KEPALA MADRASAH - Agam Hyansantang Maulana; Imron Arifin; Raden Bambang Sumarsono (Universitas Negeri Malang, 2019)
Abstract: This study was designed to describe: (1) the leadership style by the principal of madrasah; (2) responses of the madrasah community about the leadership by the principal of madrasah; (3) characteristics of Islamic prophetic leadership by the principal of madrasah; and (4) supporting factors and obstacles to Islamic prophetic leadership by the principal of madrasah. This study uses qualitative research by making a case study at MI Muhammadiyah 03 Jogoroto, Jombang Regency. Data collection used in this study using interview techniques, collection, and documentation. In data analysis, the techniques used are data collection, data reduction, data presentation, and verification. The results of this study are: (1) Islamic prophetic leadership style by the principal of madrasah; (2) madrasah responded positively to the leadership of the madrasah principal; (3) the characteristics of Islamic prophetic leadership by the principal of madrasah practicing the nature of the leadership of the Apostle (sidiq, amanah, tabligh, and fatonah); And (4) the conducive atmosphere of the madrasa, a sense of togetherness, and high commitment are supporting factors for Islamic prophetic leadership by the madrasah principal, while the inhibiting factors are human limitations and imperfections. Keywords: headmaster, leadership, prophetic leadership Abstrak: Penelitian ini bertujuan untuk mendeskripsikan mengenai: (1) gaya kepemimpinan kepala madrasah; (2) tanggapan warga madrasah mengenai kepemimpinan kepala madrasah; (3) karakteristik kepemimpinan profetik Islam oleh kepala madrasah; dan (4) faktor prndukung dan penghambat kepemimpinan profetik Islam oleh kepala madrasah. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan penelitian studi kasus di MI Muhammadiyah 03 Jogoroto Kabupaten Jombang. Pengumpulan data yang digunakan dalam penelitian ini menggunakan teknik wawancara, observasi, dan dokumentasi. Pada analisis data, teknik yang digunakan adalah pengumpulan data, reduksi data, penyajian data, dan verifikasi. Adapun hasil dari penelitian ini adalah: (1) gaya kepemimpinan profetik Islam oleh kepala madrasah; (2) warga madrasah menanggapi dengan positif mengenai kepemimpinan kepala madrasah; (3) karakteristik kepemimpinan profetik Islam oleh kepala madrasah mengamalkan sifat dasar kepemimpinan Rasul (sidiq, amanah, tabligh, dan fatonah); dan (4) lungkungan madrasah yang kondusif, rasa kebersamaan, dan tingginya komitmen menjadi faktor pendukung kepemimpinan profetik Islam oleh kepala madrasah, sedangkan faktor penghambatnya adalah keterbatasan dan ketidaksempurnaan manusia.Kata kunci: kepala madrasah, kepemimpinan, kepemimpinan profetik.